Ethics of Using Social Media Based on Religious Values for Students as an Effort to Give Birth to Digital Piety - Aulia Tasha Z. M. (LP2M UIN Sunan Kalijaga, 2025)
The use of social media has become an unavoidable phenomenon in everyday life, especially among students. However, along with technological advances, various ethical challenges arise that need to be addressed, especially from the perspective of religious values. This study aims to examine the importance of ethical use of social media based on religious values for students to foster digital piety. This research uses a qualitative approach with a descriptive method. Data were collected by distributing questionnaires and observations to students at Jambi University. The results of this study show that the majority of Jambi University students use social media throughout the day, with many of them considering religious values important in their interactions. A total of 81.8% stated that they consider religious values when choosing content to share on social media, and around 57.6% feel that social media can be a means to strengthen religious values in daily life. Expectations for achieving digital piety in this digital era include expanding da'wah networks through social media, providing training programs on the use of technology, and raising awareness of the impact of online actions. [ Penggunaan media sosial telah menjadi fenomena yang tidak dapat dihindari dalam kehidupan sehari-hari, terutama di kalangan pelajar. Namun, seiring dengan kemajuan teknologi, muncul berbagai tantangan etika yang perlu disikapi, terutama dari perspektif nilai-nilai agama. Penelitian ini bertujuan untuk mengkaji pentingnya etika penggunaan media sosial berdasarkan nilai-nilai agama bagi mahasiswa untuk menumbuhkan kesalehan digital. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Pengumpulan data dilakukan dengan menyebarkan kuesioner dan observasi kepada mahasiswa di Universitas Jambi. Hasil penelitian ini menunjukkan bahwa mayoritas mahasiswa Universitas Jambi menggunakan media sosial sepanjang hari, dengan banyak dari mereka yang menganggap nilai-nilai agama penting dalam interaksi mereka. Sebanyak 81,8% menyatakan bahwa mereka mempertimbangkan nilai-nilai agama ketika memilih konten yang akan dibagikan di media sosial, dan sekitar 57,6% merasa bahwa media sosial dapat menjadi sarana untuk memperkuat nilai-nilai agama dalam kehidupan sehari-hari. Harapan untuk mencapai kesalehan digital di era digital ini antara lain dengan memperluas jaringan dakwah melalui media sosial, menyediakan program pelatihan penggunaan teknologi, dan meningkatkan kesadaran akan dampak dari tindakan online.]